Subgaleal Drain Placement Following Intracranial Surgeries: A Prospective Observational Study on Outcomes and Complications - Ghimire, Niraj; Kolakshyapati, Manish; Tiwari, Govinda Prasad; Ghimire, Nisha (Journal of Nepalgunj Medical College, 2025)
Introduction: Subgaleal drains are commonly used following intracranial surgeries to prevent hematoma accumulation and enhance wound healing. However, there is limited evidence regarding the outcomes and complications associated with drain placement. There is also a lack of standardized protocols regarding the use of drain following craniotomies. Aims: To evaluate thepostoperative outcomes, including complication rates, duration of ICU and hospital stay following subgaleal drain placement in patients undergoing intracranial surgeries. Additionally, the aim was to correlate the patient characteristics with the duration of drain placement. Methods: A prospective observational study was conducted among 40 patients at Nepalgunj Medical College. Demographic, clinical and postoperative data were collected, including drain duration, ICU and hospital stay and complications such as cerebrospinal fluid leak, wound infection, and periorbital swelling. All data were analyzed using SPSS version 26. Results: Among 40 patients with subgaleal drains, the mean duration of drain placement was 4.55 days, with 55% of drains removed within 5 days with the threshold being <30ml/24 hrs. The most frequent complication was periorbital swelling (72%), followed by surgical site infection (30%) and wound dehiscence (27.5%). CSF leaks occurred in 10% of cases, while meningitis and pneumocephalus were rare (<5%). There was no statistically significant correlation between the patient characteristics (Age, sex, diagnosis and type of surgery) to the duration of drain placement. Conclusion: Subgaleal drain placement following intracranial surgery appears to be generally safe and effective owing to the removal of drain in less than 5 days without clinical untoward effects. There is no correlation of duration of drain placement to patient demographics and surgical parameters including postoperative complications suggesting the need of standardized early drain removal protocols. The self-limiting and minor, manageable complications like periorbital swelling, surgical site infection and wound dehiscence are most frequent complications and are independent of the drain duration placement.